2021
DOI: 10.1109/access.2021.3123152
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Design of High Resolution MEMS Gyroscope Using Mode-Localization in Weakly Coupled Resonators

Abstract: This paper presents a novel design for a high resolution microelectromechanical systems (MEMS) technology based resonant gyroscope using the mode-localization effect in weekly coupled resonators (WCRs) as a mechanism for sensing the input angular rate. The design consists of a single proof mass with two three degree-of-freedom (3-DoF) WCRs systems attached on either side. The MEMS gyroscope is designed according to the microfabrication constraints of the foundry process, silicon-oninsulator multi-user MEMS pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…In summary, we take the first-order mode of the resonant beam as the working mode. Substitute k = 1 into equation (26) and j 1 (L/2) = 1 into equation (24). After simplification, the following equation can be obtained as:…”
Section: Discretization Of Dynamic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we take the first-order mode of the resonant beam as the working mode. Substitute k = 1 into equation (26) and j 1 (L/2) = 1 into equation (24). After simplification, the following equation can be obtained as:…”
Section: Discretization Of Dynamic Equationsmentioning
confidence: 99%
“…In terms of micro-mass sensors, in 2020, Lyu et al [23] proposed a mode-localization micro-mass sensor consisting of a pair of electrostatically coupled unequallength double-ended fixed resonant beams and found that the relative sensitivity based on the amplitude ratio variation was improved by three orders of magnitude over that based on the frequency variation in the linear case. In terms of micro-gyroscopes, in 2021, Bukhari et al [24] developed a multi-DOF weakly-coupled microgyroscope using the mode-localization principle. They found that the relative sensitivity based on the amplitude ratio variation is three orders of magnitude higher than that based on the frequency variation with an angular velocity range of ±100°/s.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, to significantly improve the sensitivity of MEMS sensors, the mode localization effect of weakly coupled resonator systems (WCRS) has attracted a lot of attention [14][15][16]. Mode localization is a physical phenomenon that occurs in periodic structures [17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that using an AR based on mode localization as an output metric could increase the sensitivity of MEMS sensors by more than two orders of magnitude. In 2021, Bukhari et al [16] first combined a WCRS and traditional MEMS gyroscopes to realize the application of mode localization effects on MEMS gyroscopes, achieving a significant enhancement in mechanical sensitivity. However, there are still certain limitations in terms of dynamic range and frequency bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low deposition rates, the thickness of RF magnetron-sputtered ZnO films is often limited to a couple of micrometers or less. Moreover, the fabrication tolerance and yield of thin-film ZnO lateral-extensional mode resonators are affected by the releasing step, as the residual stress causes suspended ZnO structural layers to buckle or even fracture [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. To circumvent these issues, this work investigates the employment of a nickel thin film, which is deposited by a low-temperature electroplating process, as the acoustic structural material for the vibrating micromechanical resonator body.…”
Section: Introductionmentioning
confidence: 99%